Características físico-químicas de frutos de abobrinha-de-moita em função de doses de potássio em cobertura - Araújo, Humberto Sampaio [UNESP]; Cardoso, Antonio Ismael Inacio [UNESP]; Evangelista, Regina Marta [UNESP]; Takata, William Hiroshi Suekane [UNESP]; Silva, Ewerton Gasparetto da [UNESP] (My University, 2014)
Potassium is considered by many researchers as the nutrient responsible for fruit quality. However, there are few studies on it. The objective of this study was to evaluate the effect of potassium topdressing levels on the physicochemical characteristics of zucchini fruits (Cucurbita pepo L.), hybrid Aline. Five treatments (0, 50, 100, 200 and 400 kg ha-1 of K2O topdressing) were evaluated in a randomized complete block design with four replications. Soon after the fruit harvest, the following fruit characteristics were evaluated: macronutrient content, hydrogen potential (pH), total titratable acidity (TTA), total soluble solids (TSS), TSS/TTA ratio, percentage of reducing sugars and texture. The potassium content, pH, and TSS/TTA ratio increased in the fruits as the level of potassium increased; whereas, the TTA was reduced. The other characteristics were not influenced by the potassium levels.

O potássio é considerado por muitos pesquisadores como o nutriente relacionado à qualidade dos frutos. No entanto, são poucas as pesquisas em que este efeito do potássio é avaliado. Objetivou-se com este trabalho avaliar o efeito de doses de potássio em cobertura na qualidade físico-química de frutos de abobrinha-de-moita (Cucurbita pepo L.) híbrido Aline. Foram avaliados cinco tratamentos (0, 50, 100, 150 e 200 kg ha-1 de K2O em cobertura), no delineamento experimental de blocos casualizados, com quatro repetições. Logo após a colheita dos frutos foram avaliadas as seguintes características físico-químicas: teor de macronutrientes nos frutos, potencial hidrogeniônico (pH), acidez total titulável (ATT), sólidos solúveis totais (SST), “ratio” (relação SST/ATT), porcentagem de açúcares redutores e a textura. O teor de potássio, o pH, e a relação SST/ATT nos frutos aumentaram à medida que se aumentou a dose de potássio, enquanto a acidez total titulável reduziu. As outras características não foram influenciadas pelas doses de potássio.
Physico-chemical characteristics of zucchini fruits as a function of potassium top dressing levels
Keywords: Cucurbita pepo; Nutrient content; Total soluble solids; pH; Total titratable acidity; Texture; Cucurbita pepo; Teores de nutrientes; Sólidos solúveis totais; pH; Acidez titulável; Textura